Histological of the Epididymis after Lead (Plumbum) Exposure in Albino Mice Mus musculus - SARI, DIAH KOMALA; WIDAYANTI, GUSTI AYU; ARIFAH, NUR (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Lead or Plumbum (Pb) is a type of heavy metal-based chemicals that our body discontinue require for its proper functioning. When these chemicals enter the body in excessive amounts, they can harm the body's systems and increase the risk of cancer. Here we use albino mice Mus musculus. These small mammals often used in laboratorium research.This study to learn the effect of lead administration on the epididymal epithelium of albino Mus musculus mice. There are 18 mice divided into 3 treatment groups with 6 mice in each group (n=6). Every mouse in each group was given an intraperitoneal injection of Pb(NO³)² at a dose of 0 mgPb/kgBB, 5 mgPb/kgBBand 10 mgPb/kgBB. After 35 days, the treated mice were euthanized using the neck dislocation technique, and the epididymal epithelium was examined histologically. The findings of the study indicate that there was a reduction in the thickness of the epididymal epithelium, or thinning of the epididymal epithelium, in the group that received Pb when compared to the control group. The average tubule diameter in the control group was 7.125 mm, in 5 mbPb/kgBB it was 5.2083 mm, whereas in the 10 mgPb/kgBB treatment group, it was 4.3333 mm. This means that there was a significant difference in the thickness of the epididymal epithelium between the control group and the group given 5 mgPb/kgBB, 10 mgPb/kgBB. The results suggest that the administration of Pb is not safe for the epididymal epithelium at a dosage of 5mgPb/kgBB and 10 mgPb/kgBB